CESifo World Economic Survey February 2017 - Johanna Garnitz; Dorine Boumans; Martin Braml (CESifo World Economic Survey, 2017)
World Economic Climate: World Economic Climate continues to brighten - Advanced Economies: Advanced economies are key drivers of global recovery - Emerging and Developing Economies: Emerging and Developing Economies still underperforming - Special Topic: Free trade – What do WES experts think?
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies